Daya Dukung Lingkungan Terhadap Perkembangan Objek Wisata Air Terjun Curug Silawe di Desa Sutopati Kecamatan Kajoran Kabupaten Magelang - Rendi, Pradipta Achmad; Budi, Santoso Apik (Geo-Image, 2018)
The purpose of this research: (1) to know the carrying capacity of the environment in the waterfall attractions Curug Silawe, (2) to know the influence of environmental carrying capacity towards the development of waterfall waterfall waterfall of Silawe.Population in this research is all area of waterfall waterfall waterfall of Silawe. Sampling is done by incidental sampling technique that is respondent who is at the time of research. The number of samples taken yatu amounted to 60 people. Techniques used in data collection include observation, interview, secondary data collection, documentation.The results showed that there are 5 factors that influence the development of tourism object Curug Silawe, namely: (1) the attraction of the calculation of the parameters have a percentage of 61.6% fall into either category, (2) transportation with a percentage of 41.6% (3) accommodation with percentage of 41.6% fall into unfilled category, (4) service facility with 46, 6% percentage included in very good category, (5) infrastructure with percentage 26% included in good category.